Medical care before and during the Winter Paralympic Games in Turin 2006, Vancouver 2010 and Sochi 2014 - Gawronski, W.; Sobiecka, J. (Journal of Human Kinetics, 2015)
Medical care in disabled sports is crucial both as prophylaxis and as ongoing medical intervention. The aim of this paper was to present changes in the quality of medical care over the consecutive Paralympic Games (PG). The study encompassed 31 paralympians: Turin (11), Vancouver (12), and Sochi (8) competing in cross-country skiing, alpine skiing, biathlon and snowboarding. The first, questionnaire-based, part of the study was conducted in Poland before the PG. The athletes assessed the quality of care provided by physicians, physiologists, dieticians, and physiotherapists, as well as their cooperation with the massage therapist and the psychologist. The other part of the study concerned the athletes` health before leaving for the PG, as well as their diseases and injuries during the PG. The quality of medical care was poor before the 2006 PG, but satisfactory before the subsequent PG. Only few athletes made use of psychological support, assessing it as poor before the 2006 PG and satisfactory before the 2010 and 2014 PG. The athletes` health condition was good during all PG. The health status of cross-country skiers was confirmed by a medical fitness certificate before all PG, while that of alpine skiers only before the 2014 PG. There were no serious diseases; training injuries precluded two athletes from participation. The quality of medical care before the PG was poor, however, became satisfactory during the actual PG. The resulting ad hoc pattern deviates from the accepted standards in medical care in disabled sports.